AB0797 Ankle Fractures and Its Relationship between Osteoporosis, Diabetes and Obesity. (15th July 2016) - Rodríguez-Muguruza, S.; Prior, A.; Florido, A.; Sanint, J.; García Mira, Y.; Casas, I.; Martinez-Morillo, M.; Mateo, L.; Canellas, J.; Tena, X.; Olive, A.; Holgado, S.
Abstract : Background: Osteoporosis is a major health problem worldwide and leads to several million fractures every year. Diabetes mellitus (DM) and obesity are an increasing threat for global health. While the pathophysiology of diabetic bone disease is unknown, some recent studies have demonstrated an increased fracture risk related to type 2 DM. Type 1 DM has also been associated with a decreased bone mineral density (BMD). Objectives: To investigate the relationship between DM and obesity, and their relation to osteoporosis and ankle fractures. Methods: Retrospective study 2008–2014. Center: tertiary academic hospital with a referral area of 850, 000 inhabitants. The medical charts, dual-energy X-ray absorptiometry (DXA), radiographs and electronic data bases were retrospectively reviewed of patients seen for ankle fractures. Patients were classified in 4 groups: obesity (IMC>30), non-obesity, diabetic and non-diabetic. We compared demographic data (age, gender), mechanism of injury (high or low energy trauma), pattern of fracture (single malleolus, bimaleollar and trimalleolar), treatment of the fracture, presence of new fracture (in other localizations) and osteoporosis treatment Results: We compared a total of 65 diabetic patients (32.3% male and 67.7% female, mean age 61.8 years [DS 17.6]) with 234 non-diabetic patients (52.9% male, 47.1 female, mean age 31.5 [DS 41.7]) and 40 obese patients (37.5% male and 34.7% female, mean age 42 years [DS 21.2]) with 76 non obese patients (38.2% male, 61.8% female). The main characteristics of the study groups are presented in Table 1 . There were no differences in fracture pattern, mechanism of injury, BMD and fracture treatment among all groups. Bimaleolar fracture was the most common pattern in all groups. Diabetic group had higher frequency of a low energy trauma, osteoporosis and new fracture. New fracture was reported in 12 patients, between 3 and 48 months (after the ankle fracture). There was 5 Colles'fracture, 3 hip, 2 in other localization. One patient had two fractures (Colles and vertebral) Obese group had higher frequency of osteopenia compared with non obese. Conclusions: We did not found statistical differences between diabetic and obese compared with non diabetic or non obese patients. Ankle fracture in diabetic group could have features of osteoporotic injury including the high frequency of new fracture. Disclosure of Interest: None declared